Diffuse Reflectance Spectroscopy with Infrared Thermography for Accurate Prediction of Cellulitis - Adam B. Raff; Antonio Ortega-Martinez; Sidharth Chand; Renajd Rrapi; Carina Thomas; Lauren N. Ko; Anna C. Garza-Mayers; Allison S. Dobry; Blair Alden Parry; Richard Rox Anderson; Daniela Kroshinsky (Elsevier, 2021)
Cellulitis is frequently misdiagnosed owing to its clinical mimickers, collectively known as pseudocellulitis. This study investigated diffuse reflectance spectroscopy (DRS) alone and in combination with infrared thermography (IRT) for the differentiation of cellulitis from pseudocellulitis. A prospective cohort study at an urban academic hospital was conducted from March 2017 to March 2018. Patients presenting to the emergency department with presumed cellulitis were screened for eligibility, and 30 adult patients were enrolled. Dermatology consultation conferred a final diagnosis of cellulitis or pseudocellulitis. DRS measurements yielded a spectral ratio between 556 nm (deoxyhemoglobin peak) and 542 nm (oxyhemoglobin peak), and IRT measurements yielded temperature differentials between the affected and unaffected skin. Of the 30 enrolled patients, 30% were diagnosed with pseudocellulitis. DRS revealed higher spectral ratios in patients with cellulitis (P = 0.005). A single parameter model using logistic regression on DRS measurements alone demonstrated a classification accuracy of 77.0%. A dual parameter model using linear discriminant analysis on DRS and IRT measurements combined demonstrated a 95.2% sensitivity, 77.8% specificity, and 90.0% accuracy for cellulitis prediction. DRS and IRT combined diagnoses cellulitis with an accuracy of 90%. DRS and IRT are inexpensive and noninvasive, and their use may reduce cellulitis misdiagnosis.